Jeńcy radzieccy w Oflagu 56 w Boguszach/Prostkach (1941–1942). Portret zbiorowy, niepełny - Marcinkiewicz, Stefan Michał (1979– ) (Instytut Historii im. Tadeusza Manteuffla Polskiej Akademii Nauk, 2025)
The article discusses Soviet prisoners of war held in Oflag 56 at Bogusze/Prostki (1941–1942). The author used the remains of documentation concerning 211 people. The constructed database enabled the creation of a general, albeit incomplete, characterisation of Soviet prisoners. It was possible to determine, among other things, the age of the prisoners, their place of origin, the place of capture, the time of registration, and the subsequent camps. A significant achievement of the article is to establish the personal details of 24 soldiers buried in the POW cemetery at Bogusze. As is the case with many such places in Poland, the current commemoration does not contain the names and surnames of the people buried there. For the first time, unique photographs showing prisoners and civilians in Oflag 56 were also used.
p. 87-117
Summary in English and Russian.
Keywords: Oflag 56; Stalag I E; POWs; World War II; Bogusze/Prostki; World War, 1939-1945 - prisoners and prisons, German; World War, 1939-1945 - Nazi crimes; Soviet war prisoners - Poland - 1939-1945